Characteristics of patients with polycistic ovarian syndrome: a narrative review of the literature (Research, Society and Development, 2023)
The present study is a narrative literature review that aims to describe and analyze the characteristics of patients with polycystic ovary syndrome (PCOS). PCOS is a hormonal disorder that affects women of reproductive age and has implications in several areas, such as reproduction, endocrinology, dermatology, gynecology, cardiology and psychology. PCOS symptoms can vary, including infertility due to ovulatory dysfunction, menstrual disorders, and androgenic symptoms. In addition, PCOS is associated with risk factors such as being overweight, which increase the risk of developing diabetes mellitus, high blood pressure, obstructive sleep apnea, cancer, dyslipidemia and cardiovascular diseases. The diagnosis of PCOS can be early or late, regardless of the woman's age, and is often discovered through changes related to the syndrome, such as increased hair, skin and hair oiliness, acne, infertility, abdominal discomfort, excessive tiredness, stress and drowsiness. The most common treatment for PCOS includes the use of metformin and oral contraceptives, which help alleviate the symptoms of hyperandrogenism, regulate the menstrual cycle and reduce metabolic syndrome. This review aims to gather relevant information from scientific studies to describe and summarize the characteristics observed in patients with PCOS.